MiR-455 targeting SOCS3 improve liver lipid disorders in diabetic mice. (1st January 2020) - Fang, Shu; Feng, Jie; Zhang, Hongbin; Li, Ping; Zhang, Yudan; Zeng, Yanmei; Cai, Yingying; Lin, Xiaochun; Xue, Yaoming; Guan, Meiping
ABSTRACT: MiR-455 has been verified a key regulator of brown adipose tissue and adipose tissue-specific overexpression of miR-455 (ap2-miR-455) mice could combat high-fat-diet-induced obesity. This study is to verify overexpression of miR-455 could ameliorate the lipid accumulation and metabolism in the liver of db/db diabetic mice and explore the potential mechanisms. Diabetic mice (db/db) and control mice (db/m) were randomly divided into four groups. After overexpression of miR-455 in the liver of db/db mice, the triglycerides level in both serum and liver decreased, the lipid deposit in liver was improved, the expression of fatty acid synthase, stearoyl-CoA desaturase 1, sterol regulatory element binding protein 1c (SREBP-1c) and acetyl-CoA carboxylase (ACCα) was also significantly down-regulated. TargetScan indicated that suppressor of cytokine signalling 3 (SOCS3) is predicated to target miR-455 and the protein of SOCS3 in the liver of db/db mice after intervention was significantly decreased. The dual luciferase reporter assay showed that SOCS3 was target gene of miR-455. In vitro, in Palmitate (PA)-stimulated human normal liver (LO2) cells, transfected miR-455 mimic could significantly inhibit the expression of SOCS3, while transfected miR-455 inhibitor could up-regulate the expression of SOCS3. Transfecting LO2 cells with siRNA of SOCS3 could significantly down-regulate the protein expression of SREBP-1c and ACCα. Our study showed that overexpression of miR-455 in the liver could improve lipid metabolism in diabetic mice by down-regulating its target gene SOCS3.